(untitled) (Ustozlar uchun, 2025)
This article explores the benefits of using the Montessori Method to teach English in elementary grades. The Montessori approach, known for its emphasis on self-directed learning and hands-on activities, offers a unique and effective way to foster language acquisition skills among young learners. By creating an engaging and interactive environment, students can develop a solid foundation in English while also nurturing their creativity and independence.